Structural Proof for the First Dianion of a Polychloride: Investigation of [Cl8]2−. Issue 36 (2nd August 2016) - Brückner, Robin; Pröhm, Patrick; Wiesner, Anja; Steinhauer, Simon; Müller, Carsten; Riedel, Sebastian
Abstract: The polychloride salt [CCl(NMe2 )2 ] + 2 [Cl8 ] 2− was synthesized and crystallized in the ionic liquid [BMP]OTf. The compound was fully characterized by Raman spectroscopy as well as X‐ray single‐crystal structure determination, and represents the first example of a polychloride dianion to be described. Detailed gas‐phase and solid‐state calculations concerning the nature of the bonding situation were also performed. Abstract : Being discrete : The new polychloride salt [CCl(NMe2 )2 ] + 2 [Cl8 ] 2− (tetramethylchloroamidinium octachloride) was crystallized from an ionic liquid and fully characterized. It is the first dianion of a polychloride to be reported. Detailed quantum‐chemical calculations show the salt is made up of discrete [Cl8 ] 2− anions which do not show any tendency to build up networks through halogen bonding.